2012
DOI: 10.1051/0004-6361/201118763
|View full text |Cite
|
Sign up to set email alerts
|

C and N abundances of main sequence and subgiant branch stars in NGC 1851

Abstract: We present the first chemical analysis of stars on the double subgiant branch (SGB) of the globular cluster NGC 1851. We obtained 48 Magellan IMACS spectra of subgiants and fainter stars covering the spectral region between 3650-6750 Å to derive C and N abundances from the spectral features at 4300 Å (G-band) and at ∼3883 Å (CN). We added to our sample ∼45 unvevolved stars previously observed with FORS2 at the VLT. These two datasets were homogeneously reduced and analyzed. We derived abundances of C and N for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 79 publications
(198 reference statements)
6
69
1
Order By: Relevance
“…They measured C and N (but not O) in subgiant branch stars in NGC 1851 and found that the fainter subgiant branch had a higher C+N content than the brighter subgiant branch, 7.64 ± 0.24 and 7.23 ± 0.31, respectively. Given that the fainter subgiant branch connects to the anomalous RGB, our C+N values for the anomalous (8.45 ± 0.14) and canonical (7.52 ± 0.21) RGBs are qualitatively consistent with Lardo et al (2012), although we note that they used different diagnostics to measure N abundances compared to this study.…”
Section: Ngc 1851supporting
confidence: 73%
See 2 more Smart Citations
“…They measured C and N (but not O) in subgiant branch stars in NGC 1851 and found that the fainter subgiant branch had a higher C+N content than the brighter subgiant branch, 7.64 ± 0.24 and 7.23 ± 0.31, respectively. Given that the fainter subgiant branch connects to the anomalous RGB, our C+N values for the anomalous (8.45 ± 0.14) and canonical (7.52 ± 0.21) RGBs are qualitatively consistent with Lardo et al (2012), although we note that they used different diagnostics to measure N abundances compared to this study.…”
Section: Ngc 1851supporting
confidence: 73%
“…Therefore any conclusions we draw concerning the CNO content of subgiant branch stars in NGC 1851 will necessarily assume that the abundances we derive for RGB objects would be similar to those on the subgiant branch. That said, we can compare our average abundances for the two RGBs to measurements of subgiant branch stars by Lardo et al (2012). They measured C and N (but not O) in subgiant branch stars in NGC 1851 and found that the fainter subgiant branch had a higher C+N content than the brighter subgiant branch, 7.64 ± 0.24 and 7.23 ± 0.31, respectively.…”
Section: Ngc 1851mentioning
confidence: 87%
See 1 more Smart Citation
“…It is difficult to imagine that this could lead to a double-peaked distribution like the one observed by Marino et al (2008) in M4. We are able to explain the more uniform distribution found in NGC 1851, however (Lardo et al 2012). Details of abundance distributions will be the subject of future work.…”
Section: The Distribution Of Orbit Eccentricities and The Ratio Of Prmentioning
confidence: 74%
“…This has been observed in most, if not all, clusters. With the recent interest in NGC 1851 there have been a couple of studies of CN, on the MS (Pancino et al 2010) and the two SGBs (Lardo et al 2012). There does, however, appear to be a dearth of studies of CN in giants in NGC 1851-here we report on observations focusing on CN band strengths in the RGB and asymptotic giant branch (AGB) stars of NGC 1851.…”
Section: Introductionmentioning
confidence: 99%